Adverse effects of long-term exposure to bisphenol A during adulthood leading to hyperglycaemia and hypercholesterolemia in mice - Marmugi, Alice; Lasserre, Frederic; Beuzelin, Diane; Ducheix, Simon; Huc, Laurence; Polizzi, Arnaud; Chetivaux, Maud; Pineau, Thierry; Martin, Pascal; Guillou, Hervé; Mselli-Lakhal, Laila (Toxicology (Amsterdam), 2014)
Bisphenol A (BPA) is a suspected endocrine disruptor highly prevalent in our environment since it is used as monomer of polycarbonate plastics and epoxy resins. Recent epidemiological and animal studies have suggested that BPA exposure may influence the development of obesity and related pathologies such as type 2 diabetes, and cardiovascular diseases. However, experimental studies have often focused on short-term exposures. In this study, we investigated the effect of several months of BPA exposure on hepatic and plasma metabolic markers in adult mice. Male CD1 mice were exposed during 8 months to five different BPA doses below or equivalent to the current no observed adverse effect level (NOAEL: 5000μg/kg/day) through drinking water. Plasma lipid profiles and liver transcriptomic analysis were performed in control and BPA-treated animals. We report a specific impact of BPA exposure on glycaemia, glucose tolerance and cholesterolemia. Consistent with the hypercholesterolemia in BPA-treated animals, RT-qPCR performed on hepatic mRNA from same animals demonstrated an overexpression of key genes involved in cholesterol biosynthesis, namely, Mvd, Lss Hmgcr, and Sqle. BPA also induced the expression of the sterol regulatory element-binding proteins 2, a master regulator of hepatic cholesterol biosynthesis. As shown by the plasma lathosterol to cholesterol ratio, a surrogate marker for cholesterol biosynthesis, whole body cholesterol de novo synthesis was also increased in BPA-exposed animals. These original results are consistent with many epidemiological studies reporting on a link between BPA exposure and the onset of cardiovascular diseases.